(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction. Kidney involvement is a hallmark of systemic lupus erythematosus (SLE) and evaluation of its inflammatory response is demanding. It was the aim of the present study to evaluate the levels of CXCL10 and vitamin D in serum samples of cases with active lupus nephritis (LN). Methods. Fifty lupus patients were enrolled in our study, 25 patients had lupus nephritis and 25 patients were without evidence of LN. Thirty-nine healthy subjects were also participated as a control group. Complete biochemical and serological parameters were measured and their correlation with serum levels of vitamin D and CXCL10 were assessed in the studied groups. Results. Serum levels of CXCL10 were significantly elevated (P≤ 0.020), while vitamin D were diminished in SLE group and active LN as compared with healthy controls and SLE patients without nephritis, respectively. CXCL10 correlated with SLE disease activity index (SLEDAI) and renal activity (P < .05), while vitamin D correlated with C3 and anti-dsDNA antibody (P < .05). Based on the receiver operator characteristic (ROC) curve analysis, CXCL10 and vitamin D levels were not better than conventional biomarkers for discriminating LN patients from non-nephritis SLE patients; however, they could differentiate most of SLE cases from healthy individuals with area under the curve (AUC) ≥ 0.703 (P < .05). Conclusion. Results indicated the importance of elevated levels of CXCL10 and deficiency of vitamin D on the pathogenesis of active LN disease.